Peningkatan Hasil Belajar Matematika Melalaui Model Pembelajaran Contextual Teaching And Learning dengan Materi Pengukuran Panjang pada Siswa Kelas IV SDN Cilangkap 03 Pagi Jakarta Timur, 2018 - Rika Febrianti (Al Aqidah (Jurnal Studi Islam), 2019)
This study aims to improve the learning outcomes of mathematics through the Contextual Teaching And Learning method so that children can solve problems faced in their daily lives. This research was conducted at SDN Cilangkap 03 Pagi. Classroom action research using the Kemmis and Mc models. Taggart. The subjects of this study were 32 subjects, 16 male students and 16 students girls. The steps in this study were: 1) Planning; 2) Implementation; 3) Observations; 4) Reflection. Analysis of the data used is qualitative and quantitative. The qualitative data uses the Miles and Hubberman models. This research was conducted in two cycles, namely cycle I and cycle II. The final results of data analysis showed an increase in mathematical results, namely the pre-cycle average of 52.12%, while the first cycle was 75.32% while the second cycle was 85.73%. Then the increase from pre-cycle to cycle I is as much as 23.20% then from cycle I to cycle II as much as 10.42%.